MANAJEMEN PENGEMBANGAN KINERJA PERGURUAN TINGGI - Wiradinata, Rochanda (2011)
The performance of a university is determined by the performance of the university leaders themselves. To reach an effective performance, qualified leaders are required, that is why a special attention should be given on the quality of the leaders and main performers of education process, who at the same time are responsible toward the performance of the institution. Individual competency, creativity, and environment factors at the private universities could influence the performance of the leaders as a reflection of the private university performance they lead. Based on the theory of education administration, human resources, education organizational behavior and leadership aspects, the research method used is survey, quantitative approach by using research instrument. The research is conducted at 8 private universities in West Java; they are four private universities in Bandung and four other universities out of Bandung. Based on the result of data processing, analizing, and testing, the followings are identified: (1) Individual competency, creativity, and environment factors that are recommended to be possessed and used by the university leaders are those that have indicators collected based on theory and researches conducted by experts with excellent quality; (2) For universities ini Bandung, profile of individual competency, creativity, and environment factors is in the criteria of quite high and high. This kind of profile results in leadership profile with the criteria high, academic achievement quite high, and sustainability between quite strong and strong. For universities out of Bandung, profile of individual competency, creativity, and environment factors is in the criteria of quite high and high. This kind of profil results in leadership profil quite high, academic achievement low and sustainability between low and quite high; (3) The results of correlation analysis show that there is positive and significant relationship among individual competency, creativity, and private university environment factors and the performance in leadership profile of qualified university, academic achievement, and sustainability of private universities both at the group of universities in and out of Bandung; (4) At the group of universities in Bandung, the result of multiple regression and path analysis show that the three independent variables: individual competency, creativity and private university environment factors influence directly and positively the performance in the leadership profile of qualified university, with determinant co efficiency (R2) = 0,729, and Z = 0,520. At the group of universities out of Bandung show that the three independent variable KI, and KR inluence directly and significant too leadership profile with R2 = 0,264, and Z = 0,858; (5) At the group of universities in Bandung, the results of path and regression analysis show that leadership profile has direct, positive, and significant influence on academic achievement with R2 = 0,375 and Z = 0,790. At the group of universities out of Bandung show R2 = 0,060 with Z = 0,969; (6) At the group of universities in Bandung, the results of path and regression analysis show that leadership profile of qualified university influence directly, positively, and significantly on the sustainability of private universities with R2 = 0,498 and Z = 0,708. At the group of universities out of Bandung show R2 = 0,004 with Z = 0,997; (7) At the group of universities in Bandung, the result of path and regression analysis shows that the four independent variable: individual competency, creativity, environment factors, and leadership profile of qualified private universities influence positively and significantly to academic achievement with R2 = 0,498, Za = 0,521 and Zb = 0,708. At the goup of universities out of Bandung, the result shows that the four independent variabel: individual competency, creativity, environment factors, and leadership profile of qualified private universities influence positively and significantly to academic achievement with R2 = 0,247, Za = 0,858 and Zb = 0,868; (8) At the group of universities in Bandung, the result of analysis shows that the four independent variable: individual competency, creativity, environment factors, and leadership profile of qualified private universities influence positively and significantly to sustainability with R2 = 0,730, Za = 0,521 and Zb = 0,520. At the group of universities out of Bandung the result shows that four independent variable: individual competency, creativity, environment factors, and leadership profile of qualified private universities infuence positively and significantly to academic achievement with R2 = 0,324, Za = 0,858 and Zb = 0,822; (9) The influence of individual competency, creativity, environment factors of private university possessed by the leader to the condition of academic achievement and private university sustainability they lead are different in power. The results of difference test trough t-test shows that all variables tested: KI,KR,FL,KP-1,KP-2, and KP-3 shows probability which is lower than 0,025. It means that variable of individual competency, creativity, and environment factors at universities in Bandung are significantly different from universities out of Bandung, it also happens with the leadership profile of qualified universities, academic achievement, and sustainability.